Air Quality And Its Impact On Athlete Performance In Outdoor Training - Andi Tilka Muftiah Ridjal (Journal of Sport Education, Coaching, and Health (JOCCA), 2026)
Air quality has become an increasingly important environmental issue in sports, particularly for athletics athletes who perform regular outdoor training. Exposure to air pollutants such as particulate matter (PM?.? and PM??), ozone (O?), and other airborne contaminants may negatively affect respiratory function, aerobic capacity, and overall athletic performance. This study aimed to analyze the impact of air quality on the performance of athletics athletes during outdoor training. A quantitative correlational design was employed involving 30 competitive athletics athletes who participated in an eight-week outdoor training program. Air quality indicators, including PM?.?, PM??, O?, NO?, and Air Quality Index (AQI), were measured using portable monitoring devices. Athletic performance was assessed through VO?max, 100-meter sprint performance, recovery heart rate, and Rating of Perceived Exertion (RPE). The results showed that the average AQI during training was 87.73 ± 15.47, indicating moderate air quality conditions. Correlation analysis revealed a strong negative relationship between AQI and VO?max (r = -0.726, p < 0.01), while positive relationships were found between AQI and sprint time, recovery heart rate, and RPE. Multiple regression analysis demonstrated that air quality variables explained 66.1% of the variance in VO?max (R² = 0.661, p < 0.001). In conclusion, poor air quality significantly reduces aerobic performance, impairs recovery, and increases physiological strain among athletics athletes. Therefore, air quality monitoring should be integrated into outdoor training management to optimize athlete performance and health.